Assessment tool for visual perception deficits in cerebral visual impairment: development and normative data of typically developing children - Vancleef, K; Janssens, E; Petré, Y; Wagemans, J; Ortibus, E (Wiley, 2019)
Aim: To develop an assessment tool that measures a wide range of visual perceptual deficits common in cerebral visual impairment (CVI) and to provide normative data from typically developing children between 3 and 6 years of age. Method: Test development reflected cross‐talk between vision research and clinical relevance for CVI. The Children's Visual Impairment Test for 3‐ to 6‐year‐olds (CVIT 3–6) includes 14 subtests covering four domains of visual perception: Object Recognition, Degraded Object Recognition, Motion Perception, and Global–Local Processing. Normative data were collected from 301 typically developing children (mean age 4y 8mo [SD 9.7mo]; 148 females, 153 males). A questionnaire was administered to parents about pregnancy duration, birth, and developmental problems. Results: Average total CVIT 3–6 performance was 60.1 (SD 5.5) out of 70. The cut‐off score for normal visual perception (53) was set at the 10th centile of scores in typically developing children. Multiple regression indicated CVIT 3–6 visual perception scores increase with age for children born at 36 weeks’ gestational age or later (β=−18.03, 95% confidence interval −31.31 to −4.75). Interpretation: CVIT 3–6 is a tool to assess a wide range of visual perceptual deficits common in CVI. Age‐dependent normative data are available because we found performance increased with age. What the Paper Adds: - A test for visual perceptual deficits common in cerebral visual impairment. - Visual perceptual functions improve with age in full‐term typically developing children.